Political Necessities of the "Goal-oriented Universe" from the Perspective of the Holy Qur'an - Seyyed Mohammad Hassan Javaheri (پژوهش نامه معارف قرآنی, 2018)
The study of the position of "the Universe" as the material world has a special significance in its purposefulness or instrumentalism in politics; is acquiring of different dimensions of Universe, the purpose of politics, or is it the mean by which politicians approach it to the goals of politics? In this research, it is shown that a viewpoint has an independent view of the universe, it considers it the "goal of politics"; another group does not value the existence of the universe, and the third group considers it as "the mean" of achieving the goals beyond the prosperity of the eternal life. This study, by examining the verses of the Quran, attempts to show which group is accepted in the Qur'an and which is criticized